Composite negative electrode sheet, preparation method thereof, and lithium ion battery

CN117936703BActive Publication Date: 2026-10-27HUIZHOU LIWINON NEW ENERGY TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311764856.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-12-20
Publication Date
2026-10-27
Estimated Expiration
2043-12-20

AI Technical Summary

Technical Problem

[0003]但纯硅材料在脱嵌锂离子的过程中,当容量全发挥时会发生接近280%的体积膨胀,缺乏与之匹配的电解液和粘结剂,SEI在不断的破裂和重构、硅颗粒因粉化而失去电接触,这都共同导致了电化学装置容量的快速衰减,无法满足实际用电设备对电化学装置性能的需求

Benefits of technology

[0021]相比于现有技术,本发明的有益效果在于:本发明通过在基体材料中的硅材料层表面设置第一锂网,以及设置在第一锂网表面设置第二锂网,上层小孔隙锂网在进行电化学反应时,锂金属膨胀带来的孔隙收缩会进一步限制下层硅材料的膨胀,下层孔隙大,为硅层膨胀留空间,从而适应和缓解充放电过程中硅层的体积膨胀与结构应力。同时锂网自身亦可作为活性物质层进行补锂,提升负极材料的能量密度,还可以缓解其自身作为活性物质进行电化学反应时发生的体积膨胀。本发明的复合负极片有利于进一步抑制材料的体积膨胀,提升材料稳定性,改善锂离子电池的安全性能。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117936703B_ABST
    Figure CN117936703B_ABST
Patent Text Reader

Abstract

The application provides a composite negative electrode sheet and a preparation method thereof and a lithium ion battery, and the composite negative electrode sheet comprises: a current collector; a base material coated on at least one surface of the current collector; wherein the base material comprises a silicon material layer arranged on the surface of the current collector, a first lithium net arranged on the surface of the silicon material layer, and a second lithium net arranged on the surface of the first lithium net. Compared with the existing negative electrode sheet, two layers of lithium nets are arranged on the surface of the silicon material layer, the contraction of the pores caused by the expansion of lithium metal during the electrochemical reaction of the upper small-pore lithium net further limits the expansion of the lower silicon material, the lower pores are large, and space is left for the expansion of the silicon layer, and the lithium net itself can also serve as an active material layer to supplement lithium, thereby improving the energy density of the negative electrode material; the composite negative electrode sheet composed of the current collector and the coating layer is beneficial to further inhibiting the volume expansion of the material, improving the stability of the material, and improving the safety performance of the material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of secondary batteries, specifically to a composite negative electrode sheet and its preparation method, and a lithium-ion battery. Background Technology

[0002] Graphite, as a traditional anode material, has its theoretical specific capacity of only 372 mAh / g severely limiting the improvement of energy density. In contrast, pure silicon, with its high specific capacity (3578 mAh / g) and low delithiation potential (0.4V vs. Li+ / Li), along with the higher theoretical capacity of lithium metal anodes (up to 3860 mAh / g), has become one of the most promising new anode materials for constructing electrochemical devices with high volumetric energy density.

[0003] However, during the lithium-ion intercalation / deintercalation process, pure silicon materials undergo a volume expansion of nearly 280% when their capacity is fully utilized. Lacking a matching electrolyte and binder, the SEI (Sediment-Insulated Plate) continuously breaks down and reconstructs, and silicon particles lose electrical contact due to pulverization. All of these factors contribute to the rapid capacity decay of electrochemical devices, failing to meet the performance requirements of practical electrical equipment. Lithium metal materials are extremely reactive, and byproducts from its reaction with the electrolyte accumulate on the negative electrode. During cycling, lithium metal continuously expands and contracts in volume, increasing the impedance of the lithium metal battery, resulting in the loss of active lithium and a decrease in capacity. Furthermore, the accumulated byproducts affect lithium-ion transport, thus impacting the cycle performance of the electrochemical device.

[0004] In view of this, it is indeed necessary to provide a technical solution to the above problems. Summary of the Invention

[0005] One of the objectives of this invention is to provide a composite anode sheet to address the shortcomings of existing technologies, thereby improving the capacity performance of current anode materials and effectively solving the volume expansion problem of silicon anode materials, thus improving their structural stability and safety performance.

[0006] To achieve the above objectives, the present invention adopts the following technical solution:

[0007] A composite negative electrode sheet, comprising:

[0008] current collector;

[0009] A base material is coated on at least one surface of the current collector;

[0010] The matrix material includes a silicon material layer disposed on the surface of the current collector, a first lithium mesh disposed on the surface of the silicon material layer, and a second lithium mesh disposed on the surface of the first lithium mesh.

[0011] The pore size of the first lithium mesh is larger than that of the second lithium mesh, and the porosity of the first lithium mesh is greater than that of the second lithium mesh.

[0012] Preferably, the pore size of the first lithium mesh is 120nm to 200nm; the pore size of the second lithium mesh is 50nm to 110nm; the porosity R1 of the first lithium mesh and the porosity R2 of the second lithium mesh satisfy the following relationship: R1 > R2, and 10% ≤ R1 - R2 ≤ 35%. Preferably, the porosity R1 of the first lithium mesh and the porosity R2 of the second lithium mesh satisfy the following relationship: R1 > R2, and 10% < R1 - R2 < 35%.

[0013] Preferably, the porosity R1 of the first lithium mesh is 70-90%, and the porosity R2 of the second lithium mesh is 55-80%.

[0014] Preferably, the current collector is a copper-carbon alloy material with a copper content of 90wt% to 95wt% and a carbon content of 5wt% to 10wt%.

[0015] Preferably, the silicon material comprises elemental silicon and silicon dioxide, wherein the content of elemental silicon is 95.5 wt% to 98 wt% and the content of silicon dioxide is 2 wt% to 4.5 wt%.

[0016] Preferably, the composite negative electrode further includes a coating layer covering the surface of the matrix material.

[0017] Preferably, the coating layer comprises a polymer and glass fiber, wherein the polymer has a mass percentage of 70 wt% to 85 wt% and the glass fiber has a mass percentage of 15 wt% to 30 wt%.

[0018] Preferably, the polymer is selected from at least one of polymethyl methacrylate, polyacetylene, polyaniline, polyisoprene, and polythiophene.

[0019] Preferably, the silicon material layer, the first lithium mesh, and the second lithium mesh are all coated with carbon material.

[0020] Furthermore, a second objective of this invention is to provide a lithium-ion battery comprising the aforementioned composite negative electrode.

[0021] Compared to existing technologies, the advantages of this invention are as follows: By setting a first lithium mesh on the surface of a silicon material layer in the substrate material, and setting a second lithium mesh on the surface of the first lithium mesh, the pores of the upper small-pore lithium mesh shrink due to the expansion of lithium metal during electrochemical reactions, further restricting the expansion of the lower silicon material. The lower layer has larger pores, leaving space for the expansion of the silicon layer, thereby adapting to and mitigating the volume expansion and structural stress of the silicon layer during charging and discharging. Simultaneously, the lithium mesh itself can also serve as an active material layer to replenish lithium, increasing the energy density of the negative electrode material, and also mitigating the volume expansion that occurs when it acts as an active material during electrochemical reactions. The composite negative electrode sheet of this invention is beneficial for further suppressing the volume expansion of the material, improving material stability, and enhancing the safety performance of lithium-ion batteries. Attached Figure Description

[0022] Figure 1 This is a schematic diagram of the structure of the composite negative electrode sheet in one embodiment of the present invention.

[0023] Wherein, 1-current collector; 2-substrate material; 21-silicon material layer; 22-first lithium mesh; 23-second lithium mesh; 3-coating layer; 4-carbon coating.

[0024] Figure 2 This is the XRD pattern test image of the composite negative electrode sheet of Embodiment 1 of the present invention. Detailed Implementation

[0025] To make the technical solutions and advantages of the present invention clearer, the technical solutions of the present invention will be clearly and completely described below in conjunction with specific embodiments. Obviously, the described embodiments are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0026] According to a first aspect of the present invention, a composite negative electrode sheet is provided, comprising:

[0027] current collector;

[0028] A base material is coated on at least one surface of the current collector;

[0029] A coating layer, which covers the surface of the substrate material;

[0030] The substrate material comprises a silicon material layer disposed on the surface of the current collector, a first lithium mesh disposed on the surface of the silicon material layer, and a second lithium mesh disposed on the surface of the first lithium mesh. Compared with conventional anode sheets, the composite anode sheet of the present invention exhibits superior capacity performance, structural stability, and electrochemical performance. By disposing of two lithium meshes with different pore sizes on the silicon material layer—the lower layer having larger pores and the upper layer having smaller pores—and controlling the pore size within an optimal range, the silicon anode material can achieve high capacity while effectively suppressing its expansion problem. The carbon coating of the substrate material can improve the material's conductivity, prevent silicon particle agglomeration, and suppress silicon expansion. Furthermore, the rigid copper-carbon current collector and the polymer coating layer both contribute to suppressing the material's volume expansion, improving material stability, and enhancing its safety performance.

[0031] In some embodiments, the copper-carbon alloy current collector has a copper content of 90wt%–95wt% and a carbon content of 5wt%–10wt%; specifically, it can be a copper content of 90wt% and a carbon content of 10wt%; a copper content of 91wt% and a carbon content of 9wt%; a copper content of 92wt% and a carbon content of 8wt%; a copper content of 93wt% and a carbon content of 7wt%; a copper content of 94wt% and a carbon content of 6wt%; a copper content of 95wt% and a carbon content of 5wt%; and may include, but is not limited to, the listed values. By changing the doping ratio of the copper-carbon alloy current collector, the copper component acts as the negative electrode current collector for electron collection and conduction; the incorporation of the carbon component can provide strength and hardness to the current collector, thereby suppressing the expansion of the negative electrode matrix material and improving the stability of the negative electrode material.

[0032] In some embodiments, the silicon material in the silicon material layer includes elemental silicon and silicon dioxide, with the elemental silicon content being 95.5 wt% to 98 wt% and the silicon dioxide content being 2 wt% to 4.5 wt%. Specifically, it can be 95.5 wt% elemental silicon and 4.5 wt% silicon dioxide; 96 wt% elemental silicon and 4 wt% silicon dioxide; 96.5 wt% elemental silicon and 3.5 wt% silicon dioxide; 97 wt% elemental silicon and 3 wt% silicon dioxide; 97.5 wt% elemental silicon and 2.5 wt% silicon dioxide; or 98 wt% elemental silicon and 2 wt% silicon dioxide. The values ​​may include, but are not limited to, those listed.

[0033] In some embodiments, the silicon material layer deposition method includes magnetron sputtering ion plating, in-situ growth, electrodeposition, template method, etc.; it may include, but is not limited to, the listed deposition methods, preferably magnetron sputtering ion plating. The advantage of magnetron sputtering ion plating is that it integrates controlled sputtering and ion plating technologies, providing a solution for improving color consistency, deposition rate, and the stability of compound composition. Depending on different product requirements, heating systems, bias systems, ionization systems, etc., can be selected. The target distribution can be flexibly adjusted, resulting in excellent film uniformity. With different target materials, composite films with better performance can be deposited. The films deposited by this equipment have the advantages of strong composite force and high density, meeting the needs of high-performance film preparation.

[0034] In some embodiments, the porosity R1 of the first lithium mesh and the porosity R2 of the second lithium mesh satisfy the following relationship: R1 > R2, and 10% ≤ R1 - R2 ≤ 35%. Preferably, R1 - R2 = 15.

[0035] In some embodiments, the porosity R1 of the first lithium mesh is 70-90%, and the porosity R2 of the second lithium mesh is 55-80%; specifically, it can be R1=70%, R2=55%; R1=75%, R2=60%; R1=80%, R2=65%; R1=85%, R2=70%; R1=90%, R2=75%; and may include, but is not limited to, the listed values. By setting two layers of lithium mesh with different porosities on a silicon material layer, the lithium mesh can provide a large number of pores, allowing sufficient space for material expansion, thereby adapting to and mitigating the volume expansion and structural stress of the silicon layer during charging and discharging; the lithium mesh itself can also serve as an active material layer to replenish lithium, improving the energy density of the negative electrode material; and it can alleviate the volume expansion that occurs when it itself acts as an active material during electrochemical reactions. The lower layer has larger pores to allow space for silicon layer expansion, while the upper layer has smaller pores; the expansion of the upper lithium metal reduces the pore size, hindering the expansion of the lower silicon layer.

[0036] In some embodiments, the coating layer comprises a polymer and glass fibers, wherein the polymer has a mass percentage of 70 wt% to 85 wt%, and the glass fibers have a mass percentage of 15 wt% to 30 wt%. Specifically, the polymer may be 70 wt% and the glass fibers 30 wt%; the polymer may be 75 wt% and the glass fibers 25 wt%; the polymer may be 80 wt% and the glass fibers 20 wt%; or the polymer may be 85 wt% and the glass fibers 15 wt%. These values ​​may include, but are not limited to, those listed. Using a polymer coating layer doped with glass fibers to encapsulate and fix the matrix material not only isolates the negative electrode from the electrolyte, but the polymer fiber membrane also possesses rigidity, which can suppress the volume expansion of the matrix material. Simultaneously, the coating can better fix the shape, ensuring that slippage does not occur between the three layers of matrix material, improving the stability of the negative electrode material and enhancing its safety performance.

[0037] In some embodiments, the polymer is selected from at least one of polymethyl methacrylate, polyacetylene, polyaniline, polyisoprene, and polythiophene. Preferably, the polymer is selected from polymethyl methacrylate (PMMA). Polymethyl methacrylate is soluble in organic solvents, can form good thin films and has good dielectric properties, possesses unique electrical properties, and its power factor decreases with increasing frequency; it also has good mechanical properties, is resistant to dilute inorganic acids and alkalis, greases and oils, and has good printability.

[0038] A second aspect of this invention provides a method for preparing a composite negative electrode, comprising the following steps:

[0039] 1) Under N2 protection, metallic copper is melted at high temperature, carbon powder is added and mixed evenly, and then cast and cooled to form a copper-carbon alloy current collector;

[0040] 2) Mix elemental silicon with silicon dioxide and grind it to below micrometers to obtain a silicon mixed material. Lay the silicon mixed material on a current collector to obtain a silicon material layer.

[0041] 3) Perforate the lithium foil to form a first lithium mesh and a second lithium mesh with different porosities;

[0042] 4) Lay the first lithium mesh on the upper surface of the silicon material layer, and lay the second lithium mesh on the upper surface of the first lithium mesh;

[0043] 5) Carbon coating is applied to the matrix material under N2 protection;

[0044] 6) First, dissolve the polymer in an organic solvent, then add glass fiber to obtain a mixture, then introduce the mixture into a mold, and evaporate the solvent at a predetermined temperature to obtain a uniformly coated film; use the coated film to wrap and fix the substrate material to obtain the composite negative electrode sheet.

[0045] The composite negative electrode sheet of this invention is prepared by the above-mentioned method. By changing the doping ratio of the copper-carbon alloy current collector, the copper component acts as the negative electrode current collector for electron collection and conduction; the carbon component provides strength and hardness to the current collector, thereby suppressing the expansion of the negative electrode matrix material and improving the stability of the negative electrode material. Two layers of lithium mesh with different pore sizes are also disposed on the silicon material layer. The lithium mesh provides a large number of pores, allowing sufficient space for material expansion, thus adapting to and mitigating the volume expansion and structural stress of the silicon layer during charging and discharging. The lithium mesh itself can also serve as an active material layer to replenish lithium, increasing the energy density of the negative electrode material; it can also mitigate the volume expansion that occurs when it acts as an active material during electrochemical reactions. The lower layer has larger pores to allow space for silicon layer expansion, while the upper layer has smaller pores; the expansion of the upper lithium metal reduces the pore size, hindering the expansion of the lower silicon layer. Carbon coating is applied to the substrate material using vapor deposition (CVD) to coat the three-layer substrate material with carbon source. Due to the porosity of the lithium mesh, carbon powder / carbon layers adhere to the surface and interior of the substrate material, thus buffering volume expansion, improving the conductivity of the material, and preventing silicon agglomeration. A polymer coating layer doped with glass fiber is then used to encapsulate and fix the substrate material. This not only isolates the negative electrode from the electrolyte, but the rigidity of the polymer fiber membrane also suppresses volume expansion of the substrate material. Simultaneously, the coating better fixes the morphology, ensuring no slippage occurs between the three substrate layers, improving the stability of the negative electrode material and enhancing its safety performance.

[0046] It should be noted that the preparation method of the present invention is for silicon-containing composite negative electrode sheets. The resulting multi-layered composite negative electrode sheet has a higher capacity than other silicon-containing negative electrode sheets, while also suppressing silicon expansion, ensuring the stability of the negative electrode sheet and improving its safety performance.

[0047] According to a third aspect of the present invention, the present invention also provides a lithium-ion battery, comprising a positive electrode, a negative electrode, an electrolyte, and a separator, wherein the negative electrode is the aforementioned composite negative electrode; preferably, the lithium salt used in the electrolyte is 1M LiPF6, and the solvent is EC:DEC:DMC 3:4:3; the separator is a PP film; the positive electrode active material used in the positive electrode active material layer is a ternary material of lithium nickel cobalt manganese oxide, and the negative electrode current collector is the aforementioned copper-carbon alloy current collector.

[0048] The method for preparing the lithium-ion battery of the present invention is well known to those skilled in the art. Generally, the method for preparing the battery includes placing the battery cell into a battery case, adding electrolyte, and then sealing it to obtain the battery.

[0049] To make the technical solution and advantages of the present invention clearer, the present invention and its beneficial effects will be described in further detail below with reference to specific embodiments and accompanying drawings, but the embodiments of the present invention are not limited thereto.

[0050] Example 1

[0051] This embodiment provides a composite negative electrode sheet, including a current collector 1; a substrate material 2 coated on at least one surface of the current collector 1; a coating layer 3 coating the surface of the substrate material 2; and a carbon coating layer 4 disposed between the substrate material 2 and the coating layer 3; wherein the substrate material 2 includes a silicon material layer 21 disposed on the surface of the current collector, a first lithium mesh 22 disposed on the surface of the silicon material layer 21, and a second lithium mesh 23 disposed on the surface of the first lithium mesh 22.

[0052] The method for preparing the composite negative electrode includes the following steps:

[0053] 1) The copper-carbon alloy is prepared according to the weight percentage of 95wt% copper and 5wt% carbon. Under N2 protection, the metallic copper is melted at a high temperature of 1100-1200℃, carbon powder is added and mixed evenly, and then cast and cooled to form a layered current collector.

[0054] 2) The mixture is prepared according to the weight percentage of elemental silicon and silicon dioxide, with elemental silicon content of 98wt% and silicon dioxide content of 2wt%. The mixture is ground to below micrometers using a ball mill, and the silicon material layer is deposited on the current collector using magnetron sputtering ion plating.

[0055] 3) A porous resin mold was prepared using laser cutting technology; lithium foil was pressed under the porous mold, and perforations were made in a glove box free of water and oxygen. First and second lithium meshes with different pore sizes and porosities were fabricated using molds with different porosities.

[0056] 4) A first lithium mesh is laid on the surface of the silicon material layer. The first lithium mesh has a pore size of 150 nm and a porosity of 75%. A second lithium mesh is laid on the upper surface of the first lithium mesh. The second lithium mesh has a pore size of 80 nm and a porosity of 60%.

[0057] 5) Under N2 protection, carbon coating of the substrate material is carried out by chemical deposition.

[0058] 6) Prepare the polymer and glass fiber according to the mass percentages, with PMMA (85 wt%) and glass fiber (15 wt%). Dissolve the PMMA powder in chloroform, pour the solution into a mold, and allow the solvent to evaporate at 30–50°C to obtain a uniformly coated film. Use this coating layer to encapsulate and fix the substrate material.

[0059] The fabrication of lithium-ion batteries:

[0060] The composite negative electrode, positive electrode, separator, and electrolyte prepared above are used to manufacture a lithium-ion battery using conventional processes. The positive electrode active material used in the positive electrode active material layer is a ternary material of lithium nickel cobalt manganese oxide, and the negative electrode current collector is a copper-carbon alloy current collector. The lithium salt used in the electrolyte is 1M LiPF6, and the solvent is EC:DEC:DMC 3:4:3. The separator is a PP film.

[0061] Example 2

[0062] The difference from Example 1 is that in step 4), a first lithium mesh is laid on the surface of the silicon material layer, and the porosity of the first lithium mesh is 70%. A second lithium mesh is laid on the upper surface of the first lithium mesh, and the porosity is 60%. The rest is the same as in Example 1, and will not be repeated here.

[0063] Example 3

[0064] The difference from Example 1 is that in step 4), a first lithium mesh is laid on the surface of the silicon material layer, and the porosity of the first lithium mesh is 90%. A second lithium mesh is laid on the upper surface of the first lithium mesh, and the porosity is 60%. The rest is the same as in Example 1, and will not be repeated here.

[0065] Example 4

[0066] The difference from Example 1 is as follows: Step 4: A first lithium mesh is laid on the surface of the silicon material layer, and the porosity of the first lithium mesh is 75%. A second lithium mesh is laid on the upper surface of the first lithium mesh, and the porosity is 55%.

[0067] The rest is the same as in Example 1, and will not be repeated here.

[0068] Example 5

[0069] The difference from Example 1 is that a first lithium mesh is laid on the surface of the silicon material layer, and the porosity of the first lithium mesh is 80%. A second lithium mesh is laid on the upper surface of the first lithium mesh, and the porosity is 75%.

[0070] The rest is the same as in Example 1, and will not be repeated here.

[0071] Example 6

[0072] The difference from Example 1 is that a first lithium mesh is laid on the surface of the silicon material layer, and the porosity of the first lithium mesh is 90%; a second lithium mesh is laid on the upper surface of the first lithium mesh, and the porosity is 55%.

[0073] Example 7

[0074] The difference from Example 1 is that: in step 4), a first lithium mesh is laid on the surface of the silicon material layer, and the porosity of the first lithium mesh is 98%; a second lithium mesh is laid on the upper surface of the first lithium mesh, and the porosity is 60%.

[0075] The rest is the same as in Example 1, and will not be repeated here.

[0076] Example 8

[0077] The difference from Example 1 is that: in step 1), the copper-carbon alloy is prepared according to the weight percentage of 96wt% copper and 4wt% carbon. Under N2 protection, the metallic copper is melted at a high temperature of 1100-1200℃, carbon powder is added and mixed evenly, and then cast and cooled to form a layered current collector.

[0078] The rest is the same as in Example 1, and will not be repeated here.

[0079] Example 9

[0080] The difference from Example 1 is that: in step 1), the copper-carbon alloy is prepared according to the weight percentage of 90wt% copper and 10wt% carbon. Under N2 protection, the metallic copper is melted at a high temperature of 1100-1200℃, carbon powder is added and mixed evenly, and then cast and cooled to form a layered current collector.

[0081] The rest is the same as in Example 1, and will not be repeated here.

[0082] Comparative Example 1

[0083] The difference from Example 1 is that: in step 4), a first lithium mesh is laid on the surface of the silicon material layer, and the porosity of the first lithium mesh is 40%; a second lithium mesh is laid on the upper surface of the first lithium mesh, and the porosity is 60%.

[0084] The rest is the same as in Example 1, and will not be repeated here.

[0085] Comparative Example 2

[0086] The difference from Example 1 is that: in step 4), a first lithium mesh is laid on the surface of the silicon material layer, and the porosity of the first lithium mesh is 75%; a second lithium mesh is laid on the upper surface of the first lithium mesh, and the porosity is 95%.

[0087] The rest is the same as in Example 1, and will not be repeated here.

[0088] Comparative Example 3

[0089] The difference from Example 1 is that: in step 4), a first lithium mesh is laid on the surface of the silicon material layer, the porosity of the first lithium mesh is 75%; and a second lithium mesh is laid on the upper surface of the first lithium mesh, the porosity of which is 30%.

[0090] The rest is the same as in Example 1, and will not be repeated here.

[0091] Comparative Example 4

[0092] The difference from Example 1 is that step 1) uses conventional copper material (copper content 100wt%) to prepare copper negative electrode current collector.

[0093] The rest is the same as in Example 1, and will not be repeated here.

[0094] Comparative Example 5

[0095] The difference from Example 1 is that: in step 1), the copper-carbon alloy is prepared according to the weight percentage of 50wt% copper and 50wt% carbon. Under N2 protection, the metallic copper is melted at a high temperature of 1100-1200℃, carbon powder is added and mixed evenly, and then cast and cooled to form a layered current collector.

[0096] The rest is the same as in Example 1, and will not be repeated here.

[0097] Comparative Example 6

[0098] The difference from Example 1 is that step 5 is omitted and the matrix material is not coated with carbon particles.

[0099] The rest is the same as in Example 1, and will not be repeated here.

[0100] Comparative Example 7

[0101] The difference from Example 1 is that step 6 is omitted and the matrix material is not polymerically coated and fixed.

[0102] The rest is the same as in Example 1, and will not be repeated here.

[0103] Comparative Example 8

[0104] The difference from Example 1 is that a conventional silicon anode paste is coated on a copper-carbon alloy current collector to obtain an anode sheet.

[0105] The rest is the same as in Example 1, and will not be repeated here.

[0106] Comparative Example 9

[0107] The difference from Example 1 is that in step 4), both layers of lithium mesh on the surface of the silicon material are large-pore lithium mesh with a pore size of 150 nm and a porosity of 75%.

[0108] The rest is the same as in Example 1, and will not be repeated here.

[0109] Comparative Example 10

[0110] The difference from Example 1 is that in step 4), both layers of lithium mesh on the surface of the silicon material are small-pore lithium mesh with a pore size of 80 nm and a porosity of 60%.

[0111] The rest is the same as in Example 1, and will not be repeated here.

[0112] The following electrochemical performance tests were performed on the batteries prepared in the examples and comparative examples, respectively.

[0113] First discharge capacity test: The battery was subjected to constant current discharge test at room temperature, with a charge-discharge range of 1.0 to 3.0V and a current density range of 400 to 5000 mA / g.

[0114] Capacity retention test: The ratio of the discharge specific capacity to the initial discharge specific capacity after 500 cycles of each example and comparative battery operating at a current density of 0.2C at room temperature was tested.

[0115] Cycle capacity retention = (500th cycle discharge capacity / First cycle discharge capacity) * 100%

[0116] Thermal shock performance: Under 25℃ ambient conditions, discharge to 3.0V with a given current of 0.2C; rest for 5 minutes; charge to 4.45V with a charging current of 0.2C. When the cell voltage reaches 4.45V, switch to constant voltage charging at 4.45V until the charging current is less than or equal to the given cutoff current of 0.05C; after resting for 1 hour, place the cell in an oven. The oven temperature is increased to 135±2℃ at a rate of 5±2℃ / min and maintained for 30 minutes before stopping. The judgment criterion is that the cell does not catch fire or explode.

[0117] 60℃ High Temperature Storage Test: The battery was placed at room temperature and charged and discharged once at 0.5C (4.45V-3.0V). The discharge capacity C0 before storage was recorded. Then, the battery was charged to a full state of 4.45V with constant current and constant voltage. The thickness d1 of the battery before high temperature storage was measured using a PPG battery thickness gauge (500g). The battery was placed in a 60℃ constant temperature chamber for 14 days. After storage, the battery was removed and the thermal thickness d2 after storage was measured. The battery thickness expansion rate after 14 days of storage at 60℃ was calculated. After the battery cooled at room temperature for 24 hours, it was discharged again at 0.5C to 3.0V with constant current. Then, it was charged to 4.45V with constant current and constant voltage at 0.5C. The discharge capacity C1 and charging capacity C2 after storage were recorded. The remaining capacity rate and recovery rate of the battery after 14 days of storage at 60℃ were calculated. The calculation formula is as follows: Thickness expansion rate after 14 days of storage at 60℃ = (d2-d1) / d1*100%.

[0118] The test results are shown in Table 1 below.

[0119] Table 1

[0120]

[0121]

[0122] The XRD pattern of the composite negative electrode obtained in Example 1 was tested, and the test results are as follows: Figure 2 As shown, the XRD test spectrum of the composite negative electrode shows diffraction peaks of Si at 28.6°, 47.7°, and 55.6°, corresponding to the (111), (220), and (311) crystal planes; diffraction peaks of Cu at 43.3° and 50.4°, corresponding to the (111) and (200) crystal planes; and diffraction peaks of Li at 35.8° and 42.9°, corresponding to the (311) and (400) crystal planes.

[0123] The test results above show that:

[0124] By comparing Comparative Examples 1-7, 1-3, and 9-10, it can be seen that the present invention, by setting two lithium meshes with different pore sizes and porosities on a silicon material layer—the lower layer having larger pores and the upper layer having smaller pores—and controlling the pore size and porosity within an optimal range, can effectively improve the electrochemical performance of the material. This allows the silicon anode material to have a high capacity while effectively suppressing its expansion problem. On the one hand, the lithium mesh acts as an active material to replenish lithium; on the other hand, the large pores in the lower layer provide space for the expansion of the silicon layer, while the small pores in the upper layer allow the upper lithium metal to expand and shrink the pores, continuously sealing them, thereby hindering the expansion of the lower silicon layer.

[0125] By comparing Examples 1, 8, and 9 with Comparative Examples 4-5, it can be seen that the present invention, by incorporating carbon powder into the negative electrode copper current collector and controlling the doping ratio of carbon powder within the preferred range, can effectively enhance the strength and hardness of the current collector, thereby suppressing the expansion of the negative electrode matrix material and improving the material stability.

[0126] By comparing Example 1 and Comparative Example 6, it can be seen that by carbon coating the matrix material, the present invention can buffer volume expansion to a certain extent, improve the conductivity of the system, prevent silicon agglomeration, and effectively improve the capacity and capacity retention of the battery.

[0127] By comparing Example 1 and Comparative Example 7, it can be seen that the present invention uses a polymer coating layer doped with glass fiber to wrap and fix the substrate material, which can not only effectively solve the problem of powder shedding or falling off that may occur in lithium mesh, silicon layer and current collector, but also suppress the expansion of the substrate material. At the same time, it can also effectively isolate the substrate material from the electrolyte and prevent interfacial side reactions, so that the structural stability and safety of the silicon material layer are significantly improved.

[0128] By comparing Example 1 and Comparative Example 8, it can be seen that the silicon anode material prepared by the present invention effectively solves the volume expansion problem compared with traditional silicon powder materials, and has significantly improved capacity performance and safety.

[0129] In summary, this invention, by setting two lithium mesh layers with different porosities on a silicon material layer—the lower layer having larger pores and the upper layer having smaller pores—and controlling the pore size within an optimal range, effectively suppresses the expansion problem of the silicon anode material while maintaining high capacity. The carbon coating of the matrix material improves the material's conductivity, prevents silicon particle agglomeration, and suppresses silicon expansion. Furthermore, the rigid copper-carbon current collector and polymer coating layer both contribute to suppressing volume expansion, improving material stability, and enhancing its safety performance. The composite anode sheet provided by this invention exhibits superior capacity performance, structural stability, and electrochemical performance.

[0130] Based on the disclosure and teachings of the foregoing specification, those skilled in the art can make changes and modifications to the above embodiments. Therefore, the present invention is not limited to the specific embodiments described above, and any obvious improvements, substitutions, or modifications made by those skilled in the art based on the present invention are within the scope of protection of the present invention. Furthermore, although some specific terms are used in this specification, these terms are only for convenience of explanation and do not constitute any limitation on the present invention.

Claims

1. A composite negative electrode, characterized in that, include: current collector; A base material is coated on at least one surface of the current collector; The matrix material includes a silicon material layer disposed on the surface of the current collector, a first lithium mesh disposed on the surface of the silicon material layer, and a second lithium mesh disposed on the surface of the first lithium mesh. The pore size of the first lithium mesh is larger than that of the second lithium mesh, and the porosity of the first lithium mesh is greater than that of the second lithium mesh. The first lithium mesh has a pore size of 120nm~200nm; the second lithium mesh has a pore size of 50nm~110nm; the porosity R1 of the first lithium mesh and the porosity R2 of the second lithium mesh satisfy the following relationship: R1>R2, and 10%≤R1-R2≤35%; The porosity R1 of the first lithium mesh is 70-90%, and the porosity R2 of the second lithium mesh is 55-80%. The first lithium mesh has large pores, which provides space for the expansion of the silicon layer and helps to adapt to and alleviate the volume expansion and structural stress of the silicon layer during charging and discharging. The current collector is made of copper-carbon alloy material; The composite negative electrode further includes a coating layer covering the surface of the matrix material, the coating layer comprising a polymer and glass fiber.

2. The composite negative electrode sheet according to claim 1, characterized in that, The copper-carbon alloy material has a copper content of 90wt% to 96wt% of the current collector mass and a carbon content of 4wt% to 10wt% of the current collector mass.

3. The composite negative electrode sheet according to claim 1, characterized in that, The silicon material includes elemental silicon and silicon dioxide, wherein the content of elemental silicon is 95.5 wt% to 98 wt% of the mass of the silicon material, and the content of silicon dioxide is 2 wt% to 4.5 wt% of the mass of the silicon material.

4. The composite negative electrode sheet according to claim 1, characterized in that, The polymer is 70wt% to 85wt% of the coating layer by mass, and the glass fiber is 15wt% to 30wt% of the coating layer by mass.

5. The composite negative electrode sheet according to claim 1, characterized in that, The polymer is selected from at least one of polymethyl methacrylate, polyacetylene, polyaniline, polyisoprene, and polythiophene.

6. The composite negative electrode sheet according to claim 1, characterized in that, The silicon material layer, the first lithium mesh, and the second lithium mesh are all coated with carbon material.

7. A lithium-ion battery, characterized in that, Includes the composite negative electrode sheet as described in any one of claims 1 to 6.

Citation Information

Patent Citations

  • Lithium-rich pole piece of lithium ion battery and preparation method thereof

    CN103199217A

  • Micron silicon composite material and preparation method and application thereof

    CN114267839A